2021
DOI: 10.51441/biomedica/5-350
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Mullerian hormone and associated pregnancy outcomes in females with polycystic ovary syndrome undergoing In vitro fertilization-embryo transfer

Abstract: <p><strong>Background and Objective</strong><strong>: </strong>Polycystic ovary syndrome (PCOS) is the most common endocrine disorder among reproductive-aged women worldwide. Pregnancy in these women is highly affected by serum levels of Anti-Mullerian hormone (AMH). This study aimed to determine the association of serum AMH levels with pregnancy outcomes in females with polycystic ovary syndrome (PCOS) undergoing in vitro fertilization-embryo transfer (IVF-ET)</p> <… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Although there were more high-quality embryos transferred in the average-AMH group than in the low-AMH group, the difference in miscarriage rate was not significant among these three groups, indicating that AMH was not associated with miscarriage rate among PCOS patients. Du et al [ 25 ] also reported the early miscarriage rate in their two subgroups. The findings suggested that the rate of early miscarriage was significantly lower among the participants in the low-AMH group, with an incidence of early miscarriage of 6.67% (6/90) in the low-AMH group and 19.09% (21/110) in the high-AMH group ( p < 0.001).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Although there were more high-quality embryos transferred in the average-AMH group than in the low-AMH group, the difference in miscarriage rate was not significant among these three groups, indicating that AMH was not associated with miscarriage rate among PCOS patients. Du et al [ 25 ] also reported the early miscarriage rate in their two subgroups. The findings suggested that the rate of early miscarriage was significantly lower among the participants in the low-AMH group, with an incidence of early miscarriage of 6.67% (6/90) in the low-AMH group and 19.09% (21/110) in the high-AMH group ( p < 0.001).…”
Section: Resultsmentioning
confidence: 99%
“…Seven studies classified participants into the low-AMH group (the 0-25 th percentile), average-AMH group (the 25-75 th percentile), and high-AMH group (the 75-100 th percentile) [ 13 , 15 , 16 , 19 22 ]; three studies classified participants into the 75–90 th percentile group and 90-100 th percentile group [ 14 , 23 , 24 ]. The remaining studies did not classify participants into different groups based on AMH levels but analyzed AMH levels as a continuous variable [ 22 , 25 33 ] and thus were not included in the quantitative analysis (meta-analysis). All 19 studies used the Rotterdam criteria for the diagnosis of PCOS.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations